The Assessment of Challenges Facing the Growth of Informal Lending Groups in Tanzania. The Case of VICOBA - Shau, I. (AFRICAN JOURNAL OF APPLIED RESEARCH, 2022)
Purpose: The study aims at the assessment of challenges facing the growth of informal lending groups in Tanzania. To meet this goal three specific objectives were involved: indicators of informal lending performance, the challenges facing informal lending practices, and the procedures to foster the performance of informal lending. Design/Methodology/Approach: The study was qualitative and applied a case study approach. A case study enables the researcher to maintain holistic and meaningful features of respondents. Village Community Bank (VICOBA) was selected as a case as it represents the basic future of micro-lending in Tanzania. Purposive sampling was employed to select VICOBA groups. The study was conducted in the Coastal region at Boko Mnemela and Kilimanjaro region at Moshi rural which is familiar to the researcher and consists of many informal lending groups with different intercultural aspects. Seven groups consisting of 40 members were interviewed. An average of two members from each group were interviewed to collect qualitative data. The instrument used include interviews, focus group discussion (FGD), and observation. Content analysis and coding approaches were used to analyze the data and interpret the findings Findings: the findings observed that lack of capital, late repayment, absenteeism, lack of financial information, dropouts, group preconceptions, and business failure are the challenges facing informal lending growth. Practical implications: Micro-lending institutions should ensure proper information sharing, ability to pay, willingness, group registration, and proper assessment procedures to foster the performance of informal lending. These results will enable policymakers and Government authorities how to improve the performance of micro-lending for an effective theory of financial inclusion in creating government revenue.